Aprender em enfermagem no contexto do programa de educação pelo trabalho para a saúde - Souza, Jackeline Felix de (2014)
We started the research on the assumption that participation in the Education Program for Work and for Health has been configured as an efficient mean of learning by enabling new ways of learning in nursing, which not only stimulate critical thinking and reflective, but contribute to better discussion on the reality of health where future professionals will act. We aim to understand some of the program's contributions to the process of learning of nursing students from the perspective of complex notions of autonomy, recursion and strategy. We develop a qualitative research and case study type we use for the first data collection the documentary analysis of the reports of the program of the year of 2009 available in the Faculty of nursing with the purpose of meeting eighteen participants by the testimonials recorded in reports and invite them to participate in the research, these six accepted. The universe of the study were nine health services of the city of Cuiabá - Mato Grosso that embraced the program and where worked the subject. For the Organization and Systematization of the data field we used the technique of thematic analysis and analysis of empirical material in the basis on the Complex Thought of Edgar Morin. The results obtained pointed out four categories of analysis. The first category has shown us that the process of learning through immersion in the world of work such as provided by the program is a promising source of innovations that stimulate inventive uses of the strategy, what happens by exercise of knowledge on health in the world of concrete work, leading the student to learn more and develop the recursion, construction of the autonomy. The autonomy has built up from multiple dependencies referenced by students, established with nurses from the service, teachers, classmates and other courses and reaffirmed that participate in the program. The second category of analysis pointed out that the context is an element essential to the completion of the significant learning because it allows the joint of theoretical and practical knowledge, also promotes the transdisciplinary exercise. In the third category we have seen that work with the error as an opportunity and not as a punishment allows the establishment of new strategies that provide significant ways of learning, new actions and strategies are conceived from the situations of failures that were marked in memory of the students. In the fourth and last category we realized that significant learning is a complex process that requires different knowledge and skills interactions, reintegrating the new to the old and realized that the program provides and collaborates for the emergence of the articulation of the knowledge and of meaningful learning. We conclude that the program sets up new ways to learn for allowing different livings and experiences that involve communities, contexts, knowledge and information, creating situations that require the student to self-reflection and constant self-analysis, promoting the spiral of knowledge and thought reform by opening new, in constant motion of future and improve on what we do.